The Influence of Clinical Supervision on Teacher Growth and Performance at Islamic School - Fansori, Rosihan; Sudadi; Umi; Ramdhan, Tri wahyudi (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
This study explores the effectiveness of clinical supervision in enhancing teaching quality and teacher professionalism in secondary religious schools. Clinical supervision is viewed as a collaborative and reflective approach that offers teachers an opportunity to develop pedagogical competencies through structured guidance and constructive feedback. Employing a qualitative approach with a case study design, this research involved direct observation, in-depth interviews, and document analysis of supervision activities within the school. Findings indicate that clinical supervision not only improves teaching skills but also encourages teachers to be more reflective in their practice, fostering a dynamic and adaptive learning environment. The collaborative nature of this supervision allows teachers to receive constructive and solution-oriented feedback, driving innovation in teaching methods and building confidence. Additionally, challenges such as limited time and resources were identified, which can be mitigated through strategic planning and enhanced management support. This study concludes that clinical supervision is an effective tool for improving teaching quality and teacher professionalism, with broader applicability in strengthening teaching practices across diverse educational contexts. These findings are expected to underpin educational policy development that emphasises continuous support and professional development for teachers.